Reconstructing the Firing and Pigment Processing Technologies of Corinthian Polychrome Ceramics, 8-6th Centuries B.C.E. (14th March 2017) - Klesner, Catherine; Stephens, Jay A.; Rodriguez-Alvarez, Emilio; Vandiver, Pamela B.
ABSTRACT: Decorative, polychrome ceramics from Corinth, Greece, produced during the 8th-6th centuries B.C.E. were luxury goods widely traded throughout Greece and the Mediterranean. Corinthian pottery is the first 5-color polychrome ceramic technology, having slip-glazes in distinctive white, black, red, yellow, and purple colors, and in a variety of surface finishes from glossy, to semi-matte, to matte. The firing temperature range, 925-1075°C, was determined experimentally to be to be higher than previously reported, similar to the Corinthian amphorae and other ceramic products. This firing range is higher than that of the better known, more prestigious Athenian Black-figure and Red-figure ceramics. In this study three examples of Corinthian and one example of Athenian Black-figure ceramics from the Marie Farnsworth collection at the University of Arizona were tested and compared to thirteen clays from Corinth. Analytical techniques included Fourier-transform infrared spectroscopy (FTIR), scanning-electron microscopy with energy-dispersive spectroscopy (SEM-EDS), micro-Raman spectroscopy, and wavelength-dispersive electron microprobe (EPMA with BSE-SEM). Artisans in Corinthian workshops experimented to change the colors of the slips by varying the type and amount of iron-rich raw material, as well as the composition of the clay used as a binder and the amount of flux used as a sintering aid to promote glass formation. Corinthian artisans developed not only different recipes to produce the various colors, but also they were able to control raw-material particle size and composition to produce variations in surface luster (matte, semi-matte and glossy). This research suggests that Corinthian polychrome-slip technology was based on careful control of particle processing, of compositional control of raw materials and their admixtures, and of firing temperature. The behavior or practice of adding different ratios of pigments and glass-forming fluxes to form various optical effects implies a detailed knowledge of what happens when these are heated and fired. This is a process of experimentation focused on developing a distinctive craft practice, which produced a distinctive and highly valued material. The Corinthians developed a more complex, easily recognizable, and culturally distinctive ceramic technology that was intentionally established as a cultural brand, and probably as a luxury brand of high socio-economic value. This research deepens our understanding of the complex pigment processing and firing technologies employed in the production of Corinthian ceramics.